Antioxidant activity and inhibition of α-glucosidase from extract and fraction of leaves and stems of Vernonia amygdalina - Siahaan Rafael; I Made Artika; Waras Nurcholis (Institute of Advanced Engineering and Science, 2023)
Previous studies have shown that bitter leaf (Vernonia amygdalina Del.) has the ability as an antioxidant and an α-glucosidase inhibitor. Still, the difference in antioxidant activity and α-glucosidase inhibition based on the leaves and stems parts have not yet been determined. The effect of flavonoid-enriched extract on antioxidant activity and inhibition of α-glucosidase has not yet been determined. This research aimed to assess the impact of flavonoid-enriched extract from the leaves and stems part of the bitter leaf. The leaves and stems part of the bitter leaf were extracted using Soxhlet apparatus with 80% methanol and then underwent successive fractionation with petroleum ether, chloroform, and ethyl acetate. The crude extract and the fraction were concentrated and followed by the determination of total flavonoid, total phenolic, antioxidant activity, α-glucosidase inhibition activity, and calculated the IC50 of α-glucosidase inhibition. This research showed that chloroform-ethyl acetate leaf fraction was the best fraction with the higher total flavonoid (24.091±0.972 mg QE/g DW), total phenolic (84.299±4.589 mg GAE/g DW), diphenylpicrylhydrazyl (DPPH) antioxidant activity (33.881 μM TE/g DW), ferric reducing antioxidant power (FRAP) antioxidant activity (312.022±1.745 μM TE/g DW) and α-glucosidase inhibition activity with an IC50 value 1.23 mg/mL.